2023
DOI: 10.3389/fmicb.2023.1130891
|View full text |Cite
|
Sign up to set email alerts
|

Tell me if you prefer bovine or poultry sectors and I’ll tell you who you are: Characterization of Salmonella enterica subsp. enterica serovar Mbandaka in France

Abstract: IntroductionIn north-western France, Salmonella enterica susp. enterica serovar Mbandaka (S. Mbandaka) is most frequently isolated from bovine and dairy samples. While this serovar most often results in asymptomatic carriage, for a number of years it has caused episodes of abortions, which have serious economic consequences for the sector. Interestingly, this serovar is also isolated from Gallus gallus in the same geographic zone. Despite its prevalence in bovines in north-western France, S. Mbandaka has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 80 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Mbandaka ST413 and evolutionary insight into the dynamics of this serovar with sequences from different regions of the world. This sequence type has been implicated in foodborne outbreaks in the EU/EEA, Israel, and the UK [ 7 , 41 ] and identified in cases of salmonellosis in Brazil [ 42 ]. The recent identification of S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mbandaka ST413 and evolutionary insight into the dynamics of this serovar with sequences from different regions of the world. This sequence type has been implicated in foodborne outbreaks in the EU/EEA, Israel, and the UK [ 7 , 41 ] and identified in cases of salmonellosis in Brazil [ 42 ]. The recent identification of S .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for virulence factors, this study showed that S. Mbandaka ST413 strains carry plasmid-borne or chromosomal genes conferring resistance to several antimicrobials commonly used in both the poultry industry and human medicine, such as aminoglycosides ( aac(6′) -Iaa ), sulfonamide ( sul2 ), streptomycin ( aph(6)-Id ), tetracycline ( tetA and tetB ), and trimethoprim ( dfrA14 ) [ 41 ]. The presence of the aac(6′)-laa gene is in line with the wide distribution of aminoglycoside resistance genes among Salmonella strains of different serovars [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fenske et al showed that the clustering of various Salmonella genomes corresponds to geographical origin rather than host specificity [ 28 ]. Even within a single serovar, Mbandaka genetic lineages infecting poultry and bovine hosts were scattered along the core SNP-based phylogeny [ 43 ]. No evidence of genomic differentiation between strains of Salmonella enterica serovar Typhimurium DT160 reflecting the shape of a phylogenetic tree was reported either [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of S . Mbandaka ST143 strains, which was focused on identifying the origin of the isolates for the sake of better epidemiological surveillance, revealed no universal pattern of specialization to bovine or avian hosts, but showed a variety of clonal populations forming distinct clades [ 43 ]. Groups of strains classified according to attributed hosts differed primarily in the composition of prophages; however, specific alleles in secretion systems were found as well [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spanish and French raw reads were quality checked and filtered as described by De Sousa Violante et al 69 and with an in-house pipeline. In brief, Trimmomatic v0.40 70 was used for the trimming step, FastQC v0.11.5 to check the read quality and ConFindr v0.8.1 to identify intra-and cross-species contamination 71 .…”
Section: Methodsmentioning
confidence: 99%